PENINGKATAN HASIL BELAJAR MENGGUNAKAN MODEL PMRI PADA MATERI PENYAJIAN DATA DI KELAS IV SDN 42 TALAWI KABUPATEN PESISIR SELATAN - Akmiyanti, Wahyuni; Zainil, Melva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the low learning outcomes of students in data presentation material. This is due to teacher-centered learning, and students are less active in expressing their opinions during learning. The purpose of this study is to describe the improvement in learning outcomes using the PMRI model in data presentation material in class IV SDN 42 Talawi, Pesisir Selatan Regency. This research is a Classroom Action Research (CAR) that uses qualitative and quantitative approaches. It is carried out in two cycles, namely cycle I consisting of 2 meetings and cycle II consisting of 1 meeting. In each cycle there are four stages, namely planning, implementation, observation, and reflection. The subjects of this study were teachers and students in class IV SDN 42 Talawi, Pesisir Selatan Regency, totaling 9 people. The results of the study showed an increase in: 1) The results of observations of the Teaching Module in cycle I averaged 81.25%, increasing in cycle II to 93.75%, 2) Teacher activity in cycle I averaged 83.33% increasing in cycle II to 95.83%, 3) Student activity in cycle I averaged 83.33% increasing in cycle II to 95.83%. Student learning outcomes in cycle I averaged 70.48, increasing to 89.86 in cycle II. For the assessment of student attitudes in cycle I, there were 3 students with negative attitudes and 4 students with positive attitudes. In cycle II, there was 1 student with negative attitudes and 8 students with positive attitudes. Thus, it can be concluded that the PMRI model can improve student learning outcomes in learning data presentation material in Elementary Schools